2017
DOI: 10.1073/pnas.1608697114
|View full text |Cite
|
Sign up to set email alerts
|

Optical detection of nanometric thermal fluctuations to measure the stiffness of rigid superparamagnetic microrods

Abstract: The rigidity of numerous biological filaments and crafted microrods has been conveniently deduced from the analysis of their thermal fluctuations. However, the difficulty of measuring nanometric displacements with an optical microscope has so far limited such studies to sufficiently flexible rods, of which the persistence length ( (1), the method that consists of measuring the dispersion of a thermostated system to assess its properties has brought a plethora of scientific successes. For instance, the tracking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 43 publications
(69 reference statements)
2
14
0
Order By: Relevance
“…S2) which shows deviation from linearity even at very low field (χ v varies by more than a factor of 2 between 2 and 10 mT). Consistently, previously detailed [11] viscous drag versus magnetic torque (VD/MT) experiments (in which the magnetically driven rotational kinetics of free rods in solution is analyzed), also showed that the rod material susceptibility χ depends on H and is proportional to χ v , the constant ratio χ/χ v being simply the ratio of the magnetic nanoparticle volume fraction within the rod and in the initial ferrofluid φ/φ…”
supporting
confidence: 72%
See 4 more Smart Citations
“…S2) which shows deviation from linearity even at very low field (χ v varies by more than a factor of 2 between 2 and 10 mT). Consistently, previously detailed [11] viscous drag versus magnetic torque (VD/MT) experiments (in which the magnetically driven rotational kinetics of free rods in solution is analyzed), also showed that the rod material susceptibility χ depends on H and is proportional to χ v , the constant ratio χ/χ v being simply the ratio of the magnetic nanoparticle volume fraction within the rod and in the initial ferrofluid φ/φ…”
supporting
confidence: 72%
“…S2) of a ferrofluid suspension of negatively charged (citrated) nanoparticles (volume fraction φ v = 3.9%) obtained by VSM using a home-made apparatus, from which was deduced the log-normal distribution of the particle diameters (10-16 nm range, mean=13 nm) [16]. Following an already published protocol [11], the rods were then prepared by dialysis of a solution of the nanoparticles mixed with positively charged polymers (poly(diallyldimethylammonium chloride)) while being exposed to a ∼ 250 mT magnetic field. We used a microscopic setup equipped with magnetic tweezers designed to induce a uniform magnetic field on the sample (Fig.…”
mentioning
confidence: 99%
See 3 more Smart Citations